Strategic Brand Management and Development : creating and marketing successful brands - Lalaounis, Sotiris T., 1980- (New York, NY : Routledge, Taylor and Francis Group, 2021)
"This book explores how organisations can design brand identities, develop brand marketing programmes, measure brand performance, and sustain brand equity, combining psychological, sociological, cultural, and management perspectives. It provides numerous examples which contextualise theory"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Branding (Marketing); Brand name products -- Management; Product management